Biblical metaphor: the cosmic garden heritage - B. Green (Acta Theologica)
An inquiry into the nature of metaphor, as it has evolved since Aristotle and particularly in the late twentieth century, allows fresh consideration of biblical texts. Using as a sample trope the ancient Near Eastern and biblical figure of the cosmic garden where humans live with the gods until they are exiled, the article works out the implications of the image, using prophetic texts and cognitive theory. Briefly and generally, then, three other texts are considered: Genesis 2-3, Deuteronomy, Song of Songs, where the figure is present but signifying differently. The article closes with a consideration of how moderns may be addressed by this biblical metaphor.